Embodied knowledge in ensemble performance - McCaleb, J. Murphey (Farnham Ashgate, 2014)
Performing in musical ensembles provides a remarkable opportunity for interaction between people. When playing a piece of music together, musicians contribute to the creation of an artistic work that is shaped through their individual performances. However, even though ensembles are a large part of musical activity, questions remain as to how they function. In Embodied Knowledge in Ensemble Performance, Murphy McCaleb explores the processes by which musicians interact with each other through performance.McCaleb begins by breaking down current models of ensemble interaction, particularly those that rely on the same kind of communication found in conversation. In order to find a new way of describing this interaction, McCaleb considers the nature of the information being shared between musicians during performance. Using examples from postgraduate ensembles at Birmingham Conservatoire as well as his own reflective practice, he examines how an understanding of the relationship between musicians and their instruments may affect the way performers infer information within an ensemble. Drawing upon research from musicology, occupational psychology, and philosophy, and including a DVD of excerpts from rehearsals and performances, Embodied Knowledge provides an holistic approach to ensemble research in a manner accessible to performers, researchers and teachers.Contents: Preface; A question of ensemble; Beyond communication; A question of content; The process of performance; Reaction and inter-reaction; Reflecting on musical knowledge; Bibliography; Index.About the Author: J. Murphy McCaleb received his doctorate in performance studies from Birmingham Conservatoire after studying trombone performance and chamber music at the University of Alaska and the University of Michigan. A bass trombonist and pianist, Murphy lectures and is Programme Leader for Creative Industries at Kidderminster College.